2016
DOI: 10.3945/jn.114.202317
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Assignment of Structural Isomers of Sulfur-Containing Metabolites in Garlic by Liquid Chromatography−Fourier Transform Ion Cyclotron Resonance−Mass Spectrometry

Abstract: The ability to discriminate between such geometric isomers will be extremely useful for the chemical assignment of unknown metabolites in MS-based metabolomics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…After withdrawing the gas component (2.5 mL × 2) by a syringe to 0.5 mL of EtOAc, water (4 mL) is added to the sealed tube to dissolve the greenish solid. [22] After careful examination of each mass spectrum and comparison with available database, these five components have been characterized as 3,5-dimethyl-1,2,4-trithiolane, 3,6-dimethyl-1,2,4,5-tetrathiacyclohexane, 4,6-dimethyl-1,2,3,5-tetrathiacyclohexane, 6methyl-1,2,3,4,5-pentathiacyclohexane, and 4,7-dimethyl-1,2,3,5,6-pentathiepane, respectively. This liquid has been characterized as carbon disulfide, in consistence with our calculations.…”
Section: Resultsmentioning
confidence: 99%
“…After withdrawing the gas component (2.5 mL × 2) by a syringe to 0.5 mL of EtOAc, water (4 mL) is added to the sealed tube to dissolve the greenish solid. [22] After careful examination of each mass spectrum and comparison with available database, these five components have been characterized as 3,5-dimethyl-1,2,4-trithiolane, 3,6-dimethyl-1,2,4,5-tetrathiacyclohexane, 4,6-dimethyl-1,2,3,5-tetrathiacyclohexane, 6methyl-1,2,3,4,5-pentathiacyclohexane, and 4,7-dimethyl-1,2,3,5,6-pentathiepane, respectively. This liquid has been characterized as carbon disulfide, in consistence with our calculations.…”
Section: Resultsmentioning
confidence: 99%
“…They also govern important characters in alliums, such as color, pungency, taste, stress tolerance, and medicinal properties. A wide range of modern techniques, such as Liquid Chromatography-Mass Spectrometry (LC–MS), Gas Chromatography–MS (GC-MS), Nuclear Magnetic Resonance (NMR), LC-Fourier Transform Ion Cyclotron Resonance (FTICR)-MS, LC-tandem quadrupole (QqQ)-MS, LC-Quadrupole Time-of-Flight (QTOF)-MS/MS, and Ultrahigh Performance Liquid Chromatography-coupled Electrospray Ionization Quadrupole Time-of-Flight Mass Spectrometry (UHPLC/ESI-QTOFMS), have been used to explore, determine, and characterize the metabolic profile of Allium species ( Soininen et al, 2014a ; Soininen et al, 2014b ; Soininen et al, 2012 ; Nakabayashi et al, 2016 ; Böttcher et al, 2017 ; Molina-Calle et al, 2017 ; Hrbek et al, 2018 ; Table 4 ).…”
Section: Survey Methodologymentioning
confidence: 99%
“…Establishing a high‐throughout, high‐specificity and high‐sensitivity analytical method is necessary . Among the available analytical techniques, ultrahigh‐performance liquid chromatography coupled to Fourier transform ion cyclotron resonance mass spectrometry (UHPLC/FT‐ICR‐MS) is a powerful and reliable analytical approach for detecting and identifying drug metabolites in vivo . It can provide not only high mass accuracy/resolution and elemental composition, but also fragmentation information, which can facilitate the structural elucidation of metabolites …”
Section: Introductionmentioning
confidence: 99%
“…16,17 Among the available analytical techniques, ultrahigh-performance liquid chromatography coupled to Fourier transform ion cyclotron resonance mass spectrometry (UHPLC/FT-ICR-MS) is a powerful and reliable analytical approach for detecting and identifying drug metabolites in vivo. [18][19][20] It can provide not only high mass accuracy/resolution and elemental composition, but also fragmentation information, which can facilitate the structural elucidation of metabolites. 21 In the study reported here, a reliable approach based on UHPLC/FT-ICR-MS was established to rapidly and comprehensively analyze the metabolites and metabolic pathways of PIM in rat plasma, bile, urine and feces after oral administration.…”
Section: Introductionmentioning
confidence: 99%